A bimodal approach to thymic carcinoma with pericardial sac invasion. Issue 3 (31st March 2019) - Ahmed, Adnan; Soin, Sarthak; Patel, Sabah
Abstract : Thymic carcinoma is a rare tumour of the thymus, representing less than 1% of thymic malignancies. 1 It has an annual incidence of 0.15–0.32 per 1 00 000 person-years. 2 It is found incidentally in 30% of the patients as an opacity on chest X-ray or with non-specific complaints of persistent cough, chest pain, fatigue, shortness of breath, arm and facial swelling, and upper airway congestion related to tumour extension. We present the case of a 59-year-old man with a history of Graves' disease status post radiation treatment presenting with cough and left lingual opacity on chest X-ray, confirmed to be thymic carcinoma with pericardial invasion and lymph node metastasis. We aim to discuss the presentation, treatment modalities and outcome associated with this rare tumour.